Preliminary Review of the Effects of Electronic Medical Administration Records (eMAR) and Electronic Doctor Order Entry (CPOE) on Patient Safety Culture in the Era of Universal Health Services - Rahmat Santoso; Stefanus Nova (SOEPRA, 2019)
In the era of universal health service [UHC], medicine was always used as part of curative, preventive, and promotive. Following pharmaceutical service standards in hospitals, health centers, and pharmacies, that medicines must be managed properly, including in their use. Medication errors are a leading cause of death in many parts of the world. The factors causing the increase in medication errors related to individuals, such as heavy workload on health care facilities and pharmaceutical service facilities, are often experienced by medical staff (General Practitioners and Specialists) and pharmaceutical personnel (Pharmacists and Pharmaceutical Technical Personnel / TTK), or organizational-related factors, such as inadequate facilities and infrastructure to document medication administration records and the entry of physician orders electronically. The study was conducted cross-sectionally retrospectively, by sharing the results of an initial literature review on the impact of electronic medication administration records (eMAR) and doctor's order entry (CPOE) on patient safety. Using PubMed and Google Scholar, we search for the following terms: "eMAR", "CPOE", "medication error", and "patient safety". Our initial findings reveal that eMAR and CPOE can have an impact on the pharmaceutical workflow, and reduce medication errors, thereby increasing patient safety. Based on the initial review, eMAR and CPOE influence the insight of pharmaceutical personnel, pharmaceutical workflows and impact on patient safety. On the other hand, there is a regulatory direction which is still in the form of a Regulation of the Minister of Health Regulation on Providers of Electronic Pharmaceutical Facilities (PSEF), but it is unfortunate that "eMAR" and "CPOE" have not become clauses governed by the government. Our plan for future research is to conduct a systematic review study to further study the impact of eMAR and CPOE on patient safety.